Late interventricular septal defect after blunt chest trauma: a case report and a review of the licterature - Molardi, Alberto; Nicolini, Francesco; Spaggiari, Igino; Maestri, Francesco; Gherli, Tiziano (Acta Biomedica Atenei Parmensis, 2013)
Cardiac injuries from blunt chest trauma are usually the result of motor vehicle accidents; cardiac injuries result in 20% of such accidents, but they are also associate to mild-to-moderate sports injuries.The severity of external injuries does not necessary reflect the severity of cardiac trauma. Blunt chest trauma can cause a variety of cardiac injuries such as myocardial contusion, myocardial rupture, pericardial trauma, valvular disruption and acute myocardial infarction.We report a case of traumatic rupture of the interventricular septum caused by a blunt chest trauma following a car crash and its successful surgical repair. In this particular case the clinical signs of interventricular shunt began evident 12-14 days after the accident.